PENGARUH LATIHAN KETERAMPILAN TEMBAKAN DIDAERAH PINALTI TERHADAP AKURASI SHOOTING PADA SSB BINA BAKAT U-17 PEKANBARU - Abdi, Muhammad Zikri; ', Ramadi; Nita, Ni Putu Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Issues raised in this study is that the average ability of kicks at goal players are still weak, a lot of balls that are not targeted to the goalkeeper. This is evident from some of it is seen from several times a game or practice is followed, the goal should be created, can not be done perfectly. The shots were made by athletes could be caught by the goalkeeper or even strayed far from the goal. This research is a study with experimental treatment (Experimental), the population in this study is the athletes SSB Bina Bakat U-17 Pekanbaru. Sample in this study is the entire population of 16 people. The technique can capture data from the pre-test and post-test. The instruments used in this research is test fired the ball into goal, which aims to measure the ability of shooting. As the independent variable is the skill training shot penalty area (X) while the dependent variable is the accuracy of shooting (Y). After that, the data is processed with statistical, normality test with Liliefors test at significant level 0,05α. The hypothesis is there are significant exercise their skills against the penalty area shot shooting accuracy. Based on t test analysis produces Thitung of 4.973 and 1.753 Ttabel means Thitung> Ttabel. It can be concluded that Ha is accepted, it concludes that there is significant influence of the penalty area vocational training shot with the accuracy of shooting at Bina SSB Bina Bakat U-17 Pekanbaru.Key Word: Exercise Shot in the Penalty Area , Shooting